Document reference and citation analysis - Yap, Lina. (2013)
With knowledge growing rampantly as more papers were published, researchers are finding the task to retrieve relevant papers to their domain of research a time-consuming task. The aim for this project is to lessen the stress on searching for relevant papers with the idea that, researcher should just retrieve an article of interest, and system should based on that article recommend related articles.